Development of flipbook-based e-worksheet in differentiated learning to improve students' mathematical problem-solving skills on circle topics - Nunu Nurhayati; Nazwa Farhah; Azin Taufik (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to develop an electronic student worksheet (e-worksheet) using flipbook media to enhance students’ mathematical problem-solving skills, focusing on the topic of circles through differentiated learning strategies. The instructional content was designed to accommodate diverse learning preferences auditory, kinesthetic, and visual, as well as various levels of prior academic achievement (high, medium, and low). This study involved 35 grade XI-3 students at a high school in Kuningan Regency. Data collection included validation from subject matter and media experts, practicality evaluations by teachers and students, and analysis of students’ pre-test and post-test scores. Subject expert validation yielded a 90% approval rate, while media experts rated it at 86%. Practicality assessments showed 93% from teachers and 88% from students. The average N-Gain score was 0.79, indicating a high level of learning improvement. The conclusion of this study regarding the development of flipbook-based e-worksheet is stated to be valid, practical, and effective in improving students' mathematical problem-solving skills. This study contributes to encouraging differentiated learning practices through interesting digital devices, increasing insight and skills regarding appropriate or good and interesting worksheet for use by students, and supporting the development of adaptive learning media according to student needs, curriculum, and technological developments.